The Influence of Online Board Game (Rhetoric) towards Students' Speaking Skill: A Quasi-Experimental Study in the Eleventh Grade of SMAN 1 Ciasem - Gina Nurpalah; Muhammad Anjar Nugraha; Lusiana Suciati Dewi (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2022)
Research conducted in SMAN 1 Ciasem. This research used a quantitative and qualitative method. The data was served numerically and tested by non-parametric statistic Mann-Whitney. The design of the study was quasi-experimental. An oral test was used as the research instrument to get the data, consisting of pre-test and post-test questionnaires and observation to know the students’ attitude in Speaking Skills. Based on the explanation above the purpose of this research is to find out the influence of Online board Game (Rhetoric) towards Students’ Speaking skill. The result of the research in experiment class and control class in post-test data the significance Asymp. Sig (2-tailed) in the pre-test is 0.127, and the score is more than the significant (?) = 0.05. and the Asymp. Sig (2-tailed) in post-test is 0.319 it shows that the value is more than the significant hypothesis criteria 0.05 the result is H0 is accepted. It shows that the Correlation (R) value is 0.193a and R Square is 0.37, and the significant value from the Anovaa 402b >0.05 the result H0 Accepted. It concluded that the correlation between online board games on speaking skills affects the amount of 3,7% and other variables influence 96,3%. It means that there is no significant influence of Online Board Game (Rhetoric) towards students’ speaking skills in the other words tells that the variable X (questionnaire) then declines variable Y (post-test). However, although there is no achievement in a significant value, the results showed that the use of Online Board Game (Rhetoric) positively affected student engagement and motivation. The way the teacher manages two classes has similarities in behavior, attitude, and values. But there are deficiencies in delivering material and direct communication with students because of online learning and can affect students’ actively responding when learning begins.